Analisis Risiko dengan Metode Preliminary Hazrd Analysis pada Galangan XYZ - Butar-Butar, Marintan Nikita; Rudianto, (Jurnal Inovasi Teknologi Manufaktur, Energi dan Otomotif, 2026)
The work process at the shipyard is divided into two types of work, namely new ship building and ship repairing. In the new ship construction activities, eleven stages of work have been involved, such as lifting plates to the CNC (Computer Numerical Control) workshop, cutting plates with CNC waterjet machines, lifting materials using overhead cranes, installation and use of scaffolding, fabrication, assembly panels, manual plate cutting, erection panels, ship interior work, hull painting, and ship launching using CMB (Cimolai Mobile Boat Hauler) machines. Meanwhile, in ship repair activities, there are nine stages of work, namely lifting docking ships to the shipyard using CMB, cleaning plates with water jets, repairing the hull, replacing engines using crawler cranes, repairing superstructures, working on ship interiors, painting using roll paint, and lifting undocking ships to jetty using CMB. All of these activities are considered to have potential hazards that can endanger the safety and health of workers. Therefore, the (PHA)  Preliminary Hazard Analysis method is used because it is considered to be able to provide an initial overview of potential risks in a systematic manner. These risks have been identified through direct observation and the questionnaires to workers involved in the production process. Once a potential hazard is identified, a risk assessment is carried out taking into account the likelihood and severity of the impact. These risks are then classified based on priority levels to determine appropriate controls. Risk control is designed based on the principle of a control hierarchy, starting from hazard elimination and substitution, technical engineering, administrative control, to the use of personal protective equipment (PPE).